Temporal Expression of Apelin/Apelin Receptor in Ischemic Stroke and its Therapeutic Potential - Wu, Yili; Wang, Xin; Zhou, Xuan; Cheng, Baohua; Li, Gongying; Bai, Bo (Frontiers in Molecular Neuroscience, 2017)
Stroke is one of the leading causes of death and disability worldwide, and ischemic stroke accounts for approximately 87% of cases. Improving post-stroke recovery is a major challenge in stroke treatment. Accumulated evidence indicates that the apelinergic system, consisting of apelin and apelin receptor, is temporally dysregulated in ischemic stroke. Moreover, the apelinergic system plays a pivotal role in post-stroke recovery by inhibiting neuronal apoptosis and facilitating angiogenesis through various molecular pathways. In this review, we summarize the temporal expression of apelin and apelin receptor in ischemic stroke and the mechanisms of their dysregulation. In addition, the protective role of the apelinergic system in ischemic stroke and the underlying mechanisms of its protective effects are discussed. Furthermore, critical issues in activating the apelinergic system as a potential therapy will also be discussed. The aim of this review is to shed light on exploiting the activation of the apelinergic system to treat ischemic stroke.